2016
DOI: 10.3109/13814788.2016.1145650
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of flurbiprofen 8.75 mg spray in patients with sore throat due to an upper respiratory tract infection: A randomised controlled trial

Abstract: Pharyngitis (sore throat) is usually caused by viral infections; therefore, antibiotics are generally not warranted. Flurbiprofen 8.75 mg spray (maximum five doses/day, for three days) provides effective symptomatic relief. ABSTRACTBackground: Viral infections cause most cases of pharyngitis (sore throat); consequently, antibiotics are generally not warranted. However, a treatment targeting pain and inflammation, e.g. a topical non-steroidal anti-inflammatory spray, may be helpful for patients. Objective: To e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
49
0
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(62 citation statements)
references
References 25 publications
4
49
0
9
Order By: Relevance
“…Our findings support those of previous studies demonstrating that flurbiprofen 8.75 mg provides effective symptomatic relief of sore throats due to URTI when delivered as either a lozenge3,20–24 or a spray 17. Previous studies have compared flurbiprofen 8.75 mg lozenge or spray with placebo.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Our findings support those of previous studies demonstrating that flurbiprofen 8.75 mg provides effective symptomatic relief of sore throats due to URTI when delivered as either a lozenge3,20–24 or a spray 17. Previous studies have compared flurbiprofen 8.75 mg lozenge or spray with placebo.…”
Section: Discussionsupporting
confidence: 90%
“…To our knowledge, our study is the first that directly compares the relief provided by flurbiprofen 8.75 mg, using two different formats in the same study population. Although this study only monitored efficacy for up to 2 hours post-dose to determine non-inferiority, previous studies have shown that both formulations provide relief for up to 6 hours post-dose,3,17 suggesting that patients may be able to resume normal activities quickly without the need for regular redosing 17…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations